Achromobacter xylosoxidans (Alcaligenes xylosoxidans subsp. xylosoxidans) meningitis associated with a gunshot wound. - D'Amato, R F (1988)
The microbiological and clinical features of a case of Achromobacter xylosoxidans (Alcaligenes xylosoxidans subsp. xylosoxidans) meningitis associated with a gunshot wound are described. To our knowledge, this is the third confirmed case report of meningitis caused by this organism.